Statistical properties of single sodium channels (The Rockefeller University Press, 1984)
Single channel currents were obtained from voltage-activated sodium channels in outside-out patches of tissue-cultured GH3 cells, a clonal line from rat pituitary gland. In membrane patches where the probability of overlapping openings was low, the open time histograms were well fit by a single exponential. Most analysis was done on a patch with exactly one channel. We found no evidence for multiple open states at -25 and -40 mV, since open times, burst durations, and autocorrelation functions were time independent. Amplitude histograms showed no evidence of multiple conductance levels. We fit the gating with 25 different time-homogeneous Markov chain models having up to five states, using a maximum likelihood procedure to estimate the rate constants. For selected models, this procedure yielded excellent predictions for open time, closed time, and first latency density functions, as well as the probability of the channel being open after a step depolarization, the burst duration distribution, autocorrelation, and the distribution of number of openings per record. The models were compared statistically using likelihood ratio tests and Akaike's information criterion. Acceptable models allowed inactivation from closed states, as well as from the open state. Among the models eliminated as unacceptable by this survey were the Hodgkin-Huxley model and any model requiring a channel to open before inactivating.